Development of heterocyclic-based anticancer agents: A comprehensive review - Al-Jumaili Mohammed Hadi Ali; Bakr Ekhlas Aziz; Huessien Mohanad A.; Hamed Ahmed Solaiman; Muhaidi Mohammed J. (Heterocyclic Communications, 2025)
This review article summarizes the role of heterocyclic compounds as anticancer drugs used against various human cancers, including doxorubicin, cisplatin, paclitaxel, and resveratrol, which are among the most effective therapeutic agents. Chemotherapy, a treatment modality, exerts its effects on tumor cell DNA and often involves the use of low-molecular-weight medicines to selectively target and destroy cancer cells. However, systemic chemotherapy is associated with several side effects, such as nausea, vomiting, myelosuppression, and cardiotoxicity. Cancer remains one of the most prevalent and lethal diseases, characterized by uncontrolled cell division and abnormal cell growth driven by multiple genetic mutations. The etiopathogenesis of cancer is complex, but significant advancements have been made in treatment, particularly with the discovery of anticancer drugs, including cytotoxic chemotherapy, hormonal agents, and targeted therapies. Anticancer drugs are widely employed for the treatment of various cancers, such as breast, cervical, uterine, and kidney cancers. These drugs are classified into several categories, including alkylating agents, antimetabolites, antibiotics, and topoisomerase inhibitors. Among these, numerous heterocyclic compounds have shown promising anticancer properties. The goal of this review is to compile information on heterocyclic compounds used as anticancer drugs, highlighting their positive effects and therapeutic targets in cancer treatment and chemoprevention.